Change in gait biomechanics after total ankle replacement and ankle arthrodesis: a systematic review and meta-analysis. (March 2020) - Deleu, Paul-André; Besse, Jean-Luc; Naaim, Alexandre; Leemrijse, Thibaut; Birch, Ivan; Devos Bevernage, Bernhard; Chèze, Laurence
Abstract: Background: The aim of this systematic review with meta-analysis was to determine the change in gait biomechanics after total ankle replacement and ankle arthrodesis for end-stage osteoarthritis. Methods: Electronic databases were searched up until May 2019. Peer-reviewed journal studies including adult participants suffering from end-stage ankle osteoarthritis and reporting pre- and post-operative kinematics, kinetics and spatio-temporal effects of total ankle replacement and ankle arthrodesis during walking were included with a minimum of 12 months follow-up. Seventeen suitable studies were identified and assessed according to methodological and biomechanical qualities. Meta-analysis was performed by calculating the effect size using standard mean differences between pre- and post-operative gait status. Findings: Seventeen studies with a total of 883 patients were included. Meta-analysis revealed moderate evidence of an improvement in lower limb kinematics, kinetics and spatio-temporal parameters after total ankle replacement. Moderate evidence indicated an increase in ankle moment, hip range of motion and walking speed after ankle arthrodesis. Interpretation: The currently available evidence base of research papers evaluating changes in gait biomechanics after total ankle replacement and ankle arthrodesis is limited by a lack of prospective research, low sample sizes and heterogeneity in the patho-etiology of ankle osteoarthritis. Following total ankle replacement, improvements were demonstrated for spatio-temporal, kinematic and kinetic gait patterns compared to the pre-operative measures. Improvements in gait mechanics after ankle arthrodesis were limited to walking speed and ankle moment. Increased hip range of motion after ankle arthrodesis could represent a sign of compensation for the lack of ankle motion. Highlights: Moderate evidence to suggest that lower extremity biomechanics improved after total ankle replacement. Moderate evidence to suggest that total ankle replacement improves pre-operative ankle range of motion by 3°. No difference in outcomes between fixed- versus mobile-bearing prosthesis Ankle moment, hip range of motion and walking speed increased after ankle arthrodesis.